(untitled) - Elmiger, Daniel (Romanica Olomucensia, 2013)
This article attempts to establish a connection between linguistics and psychoanalysis, using as an example the genericity of masculine forms, a topic which is central, in French, in the debate about the "féminisation des textes" (i. e. avoiding generically used masculine forms) and which seems to be collectively repressed as opposed to the "féminisaton du lexique" (i. e. the coining of female-specific nouns. Moreover, the conceptualisation of the << creation >> of female-specific nouns (by means of an inflexional or derivational process) is discussed and exemplified by analogy with the two narrations of the creation of the first humans in Genesis (chapter 1).
Keywords: lexical feminisation; nonsexist language; generic masculine; flexion; derivation; Bible; psychanalysis.